Coagulation and dynamics nanoparticles in low pressure plasma jets - Kravchenko, O.Yu.; Maruschak, I.S. (Вопросы атомной науки и техники, 2019)
One of the most promising methods for creating nanostructured films is the use of plasma jets of low pressure with nanoparticles. In this case, it is important to control the size of the nanoparticles, their temperature and energy to optimize the properties of the films. In this paper, using computer simulations, a study is conducted on coagulation of nanoparticles in a plasma jet that expands into rarefied gas. In our model, we use a hydrodynamic model for describing the dynamics of a plasma with a multidisperse phase, as well as a sectional method for describing the coagulation of nanoparticles. At the entrance to the plasma torch, the plasma parameters were stationary, and the dust particles were considered the same size. Calculations were made at various concentrations of dust particles in the plasma jet. The simulation results show that nanoparticles of various sizes appear in the plasma stream as a result of coagulation. With increasing distance from the inlet, the average modulus charge and the dispersion of the charge of nanoparticles decreases due to the decrease in the temperature of the ions and, consequently, the ion current on the dust particles.